FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI REMAJA FORUM ANAK KABUPATEN SERANG - Muhammad Rafli Nurdianto; Herlina Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the factors influencing adolescent motivation in organizations, using a case study of the Serang Regency Children's Forum. Motivation is a crucial element in volunteer organizations, determining the sustainability of member participation without financial compensation. The research method used was descriptive qualitative through in-depth interviews with leaders and division coordinators. The results showed that informants' motivation was dominated by intrinsic and non-material factors. Based on Malayu S.P. Hasibuan's (2020) motivation theory, it was found that (1) Physical needs were set aside for the sake of achieving social goals; (2) Security needs were met through administrative legality and assistance from relevant agencies; (3) Social needs became a bond through solid friendships; and (4) Appreciation needs were met through validation of competence and trust in decision-making. In conclusion, fulfilling higher-level psychological needs and implementing appropriate motivational principles by organizations proved more effective in maintaining adolescent loyalty and work enthusiasm than material incentives. This study recommends strengthening institutional support and providing meaningful participation spaces for adolescents as key strategies in the management of volunteer organizations.